Student perceptions of ecuadorian virtual platforms during the Covid-19 pandemic - Mendoza Velazco, Derling José (2021)
In February 2020 Ecuador declared a health emergency due to the Covid-19 pandemic. On-site classes were suspended. The Ecuadorian university population does not adapt to virtual educational platforms. The objective of the study was to analyse student perception of Ecuadorian educational platforms in higher education during the COVID-19 pandemic. The study was quantitative. The sample was non-probabilistic participatory, consisting of students from different universities in the Province of Chimborazo. For data collection, a questionnaire with four study variables was applied. The results were analysed with T student and MANOVA. There is a positive perception of students using the educational platforms. There were significant statistical differences according to gender variables, contrary to the levels of study and location, there is a greater sympathetic affection of students when receiving virtual classes by female teachers. It can be concluded that the Covid-19 pandemic accelerated the adoption of online learning by higher education institutions.